PENGEMBANGAN PERMAINAN KOTAK BARISAN YANG DIGUNAKAN PADA KEGIATAN APERSEPSI MATERI BARISAN DAN DERET UNTUK MENINGKATKAN MOTIVASI SISWA KELAS X SMA - Palupi, Elis Widyo (Jurnal Pembelajaran Matematika, 2017)
The aim of the development is to describe a valid, practical and effective process and the result of the development of Kotak Barisan game used in "Series and Sequence" apperception activity for enhancing the tenth grade studentsâ motivation. Development model that is used is Plomp model consisting of three stages, which are preliminary research, prototyping phase, and assessment phase. The result is, based on the analysis, the validity reaches 80,5% belonging to level of valid. Three-instrument practicality test shows that the game belongs to the level of practice. Then, comparing the result of effectivity test, the number of motivated students increase for 4 students compared to prior to do the test. Hence, Kotak Barisan game enhances motivation effectively